2013
DOI: 10.5194/bgd-10-6671-2013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Solute specific scaling of inorganic nitrogen and phosphorus uptake in streams

Abstract: Stream ecosystem processes such as nutrient cycling may vary with stream position in the watershed. Using a scaling approach, we examined the relationship between stream size and nutrient uptake length, which represents the mean distance that a dissolved solute travels prior to removal from the water column. Ammonium uptake length increased proportionally with stream size measured as specific discharge (discharge/stream width) with a scaling exponent = 1.01. In contrast, the scaling exponent for nitrate… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
1
1

Year Published

2015
2015
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(64 citation statements)
references
References 37 publications
4
58
1
1
Order By: Relevance
“…Sheibley et al (2014) did not measure any in-stream SRP uptake at all, as was also the case in some of the Weinviertel streams. In their review about 969 nutrient uptake experiments, Hall et al (2013) observed that SRP uptake lengths were generally longer in human-impacted streams than in pristine systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sheibley et al (2014) did not measure any in-stream SRP uptake at all, as was also the case in some of the Weinviertel streams. In their review about 969 nutrient uptake experiments, Hall et al (2013) observed that SRP uptake lengths were generally longer in human-impacted streams than in pristine systems.…”
Section: Discussionmentioning
confidence: 99%
“…Comprising about two-third of the total river length in European countries and the U.S. (Kavanagh & Harrison, 2014;Kristensen & Globevnik, 2014), small headwater streams are important links between the catchment and downstream reaches (Reddy et al, 1999;Dodds & Oakes, 2008). Due to their usually diverse channel morphology and their low discharge, pristine headwater streams can retain and process large amounts of nutrients and organic carbon from the catchment, thereby controlling matter transport into the remaining river system (Hall et al, 2002;Alexander et al, 2007;Hall et al, 2013). This retention function has become increasingly important in the face of the expansion and intensification of agriculture during the twentieth century (Gordon et al, 2008;Withers & Jarvie, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…By comparing our water column v f measurements to reach-scale v f from a recently compiled meta-analysis (Hall et al 2013), we find that water column demand is lower than reach-scale demand, but the ranges overlapped for each solute (Fig. By comparing our water column v f measurements to reach-scale v f from a recently compiled meta-analysis (Hall et al 2013), we find that water column demand is lower than reach-scale demand, but the ranges overlapped for each solute (Fig.…”
Section: Responsementioning
confidence: 99%
“…The relationship between suspended inorganic sediments and v f-SRP may reflect Fig. Reach-scale studies were compiled from Hall et al (2013) and included any non-isotope study which reported v f . Reach-scale studies were compiled from Hall et al (2013) and included any non-isotope study which reported v f .…”
Section: Responsementioning
confidence: 99%
See 1 more Smart Citation